Padrões espaço-temporais de coocorrência em assembleias de peixes de uma planície de inundação neotropical. - Ortega, Jean Carlo Gonçalves (2014)
A community can be structured by deterministic, stochastic or both mechanisms along time. It was assessed if the fish assemblage of upper Paraná River floodplain is spatial-temporally structured and which main mechanisms are driving these organizational patterns. The floodplain ichthyofauna was sampled quarterly with seine and gillnet. The assemblage structure was assessed with the C-Score index and null models. The influence of the environment (physicochemical variables and the river level) and time on co-occurrence was assessed by principal component analysis, multiple and simple regressions and analysis of variance. Assemblages with large sized species showed patterns of species segregation in spatial and temporal scales, while those composed of small sized species often exhibit random patters. Environmental predictors did not predict co-occurrence among species. Patterns of co-occurrence tended to be random as the river level increases, only in the assemblage of large sized species in high water months. The structure of these assemblages might be influenced by life history traits of the species that compose the assemblage, and that temporally they are subjected to an assembly and disassembly dynamics following a hydrometrical gradient.